(3x-12)+(5x-34)=90

Simple and best practice solution for (3x-12)+(5x-34)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-12)+(5x-34)=90 equation:


Simplifying
(3x + -12) + (5x + -34) = 90

Reorder the terms:
(-12 + 3x) + (5x + -34) = 90

Remove parenthesis around (-12 + 3x)
-12 + 3x + (5x + -34) = 90

Reorder the terms:
-12 + 3x + (-34 + 5x) = 90

Remove parenthesis around (-34 + 5x)
-12 + 3x + -34 + 5x = 90

Reorder the terms:
-12 + -34 + 3x + 5x = 90

Combine like terms: -12 + -34 = -46
-46 + 3x + 5x = 90

Combine like terms: 3x + 5x = 8x
-46 + 8x = 90

Solving
-46 + 8x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '46' to each side of the equation.
-46 + 46 + 8x = 90 + 46

Combine like terms: -46 + 46 = 0
0 + 8x = 90 + 46
8x = 90 + 46

Combine like terms: 90 + 46 = 136
8x = 136

Divide each side by '8'.
x = 17

Simplifying
x = 17

See similar equations:

| (3cosx)*(2cosx)= | | 3x/6=7x-6x/2 | | -4.6x+2.3=-20.7 | | Sin64=16/x | | x+3x-12+5x-34=180 | | -4x-45=39 | | 6x+4y=3.5 | | 3(x+4)-2(2+2x)=3(x-6+12+2) | | 9-2(x+4)=8(3-x)+1 | | -14.3=-1.8-3D | | 5-22=5x-4-4x | | 9×1/1000 | | 14x+9y=18p | | -150=-6(1-6x) | | 15u=135 | | x-2x=5+x | | 20th-8x=x-8 | | y=cos3/4x | | .2x+x^2=0 | | 5x+10y=166 | | 9y-7+18=2 | | (.2+x)x=0 | | (2.3x+25)=(5.8x+11) | | (.2+x)x=x^3 | | X-98=258 | | -8m-[3m(11+4m)+2]=9m | | 7y-42(0)+7=0 | | -3=6n-5n | | -69+11x=x+61 | | w-2-3h=52 | | 8x-14=(x^2)+1 | | 4x+-4x=-1x+-1 |

Equations solver categories